2002
DOI: 10.1002/j.1875-595x.2002.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methyl mercaptan on epithelial cell growth and proliferation

Abstract: High concentrations of CH3SH such as 50 ng/ml have an inhibitory effect on the growth and proliferation of epithelial cells, but not on those of fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…26,35,36 These compounds increase cathepsin B and cAMP, secretion of PGE 2 , and permeability of the oral mucosa, decrease protein and collagen synthesis, and inhibit growth and proliferation of epithelial cells. [37][38][39][40][41] It has also been shown that exposure to methyl mercaptan alters protein synthesis in human gingival fibroblasts, inhibits cell migration, and reduces intracellular pH in periodontal ligament cells. 42,43 On the basis of a previous report, 30 it seems that most strains of H. pylori require sulfur-containing amino acids and can produce VSCs.…”
Section: Discussionmentioning
confidence: 98%
“…26,35,36 These compounds increase cathepsin B and cAMP, secretion of PGE 2 , and permeability of the oral mucosa, decrease protein and collagen synthesis, and inhibit growth and proliferation of epithelial cells. [37][38][39][40][41] It has also been shown that exposure to methyl mercaptan alters protein synthesis in human gingival fibroblasts, inhibits cell migration, and reduces intracellular pH in periodontal ligament cells. 42,43 On the basis of a previous report, 30 it seems that most strains of H. pylori require sulfur-containing amino acids and can produce VSCs.…”
Section: Discussionmentioning
confidence: 98%
“…As 60 ppb-0.6 ppm of sulfide were demonstrated in the culture medium utilized for experiments that examined the adverse effects of VSCs on human cell cultures, these studies, which were discussed in this paper, could simulate of the conditions of human tissues [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Total VSCs or H 2 S concentration in mouth air from healthy subjects is reported as a maximum of 2 ppm or 1 ppm, while several times this concentration is found in periodontal patients [4,33,34].…”
Section: Toxicity Of Vscs In General Conditionsmentioning
confidence: 99%
“…The host factors of periodontitis are clearly identified, but the etiology of periodontitis has not yet been explicitly illustrated, especially at its initial stage [7]. It has been recently elucidated that VSCs reduce the effectiveness of the gingival epithelial tissues that normally play a key role as a barrier against penetration and invasion by detrimental compounds and microorganisms [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies showed that increased levels of VSCs have pathogenic potential and may play an important role in the etiology of periodontitis. H 2 S has been shown to inhibit collagen synthesis [98], inhibit proliferation of epithelial cells [99] and the synthesis of basal membranes [100], and decrease total protein production in oral fibroblasts [101]. Osteoclast activation following increased levels of VSCs both in vitro and in rat alveolar bone has also been reported [102,103].…”
Section: Ppmmentioning
confidence: 95%